Turning shy on a winter's day: Effects of season on personality and stress response in Microtus arvalis - Gracceva, Giulia; Herde, Antje; Groothuis, Ton G. G.; Koolhaas, Jaap M.; Palme, Rupert; Eccard, Jana (Prof. Dr.) (Ethology, 2014)
Animal personalities are by definition stable over time, but to what extent they may change during development and in adulthood to adjust to environmental change is unclear. Animals of temperate environments have evolved physiological and behavioural adaptations to cope with the cyclic seasonal changes. This may also result in changes in personality: suites of behavioural and physiological traits that vary consistently among individuals. Winter, typically the adverse season challenging survival, may require individuals to have shy/cautious personality, whereas during summer, energetically favourable to reproduction, individuals may benefit from a bold/risk-taking personality. To test the effects of seasonal changes in early life and in adulthood on behaviours (activity, exploration and anxiety), body mass and stress response, we manipulated the photoperiod and quality of food in two experiments to simulate the conditions of winter and summer. We used the common voles (Microtus arvalis) as they have been shown to display personality based on behavioural consistency over time and contexts. Summer-born voles allocated to winter conditions at weaning had lower body mass, a higher corticosterone increase after stress and a less active, more cautious behavioural phenotype in adulthood compared to voles born in and allocated to summer conditions. In contrast, adult females only showed plasticity in stress-induced corticosterone levels, which were higher in the animals that were transferred to the winter conditions than to those staying in summer conditions. These results suggest a sensitive period for season-related behavioural plasticity in which juveniles shift over the bold-shy axis.